A case study of blended teaching and learning in a New Zealand secondary school, using an ecological framework - Pinelopi Zaka (Flexible Learning Association of New Zealand, 2013)
This paper reports on the findings of a case study that investigated how blended teaching and learning was implemented in a New Zealand secondary school. An ecological perspective was taken, in an attempt to clarify the complexity of blended teaching and learning implementation, by researching the roles of students, teachers, school leaders and other educational stakeholders, within and beyond the school itself. An ecological framework was developed that gives rise to several recommendations for individuals and groups within the three levels of the school's multi-level ecology; the classroom, the school and the wider ecosystem in which the school is embedded.